Incretin-based therapies for type 2 diabetes mellitus in Asian patients: Analysis of clinical trials (Faculty of Medicine Universitas Indonesia, 2010)
Aim To review the effi cacy and safety data on incretin-based therapies currently available (exenatide, liraglutide, sitagliptin, vildagliptin) for the treatment of type 2 diabetes mellitus in Asian population. Methods We conducted Medline search of all relevant randomized clinical trials of incretin-based therapies for type 2 diabetes mellitus in Asian populations. Data pertinent to the efficacy and safety of GLP-1 mimetics and DPP-4 inhibitors were extracted and used. Results We found 14 randomized controlled trials of incretin based-therapy which included 3567 type 2 diabetes mellitus in Asian population (Japanese, Chinese, Korean, Indian). It was shown that incretin-based therapies improved HbA1c at higher extent (up to -1.42% in exenatide 10 mcg bid, -1.85% for liraglutide 0.9 mg qd, -1.4% for sitagliptin 100 mg and -1.4% for vildagliptin 50 mg bid) compared to the effects observed in studies with Caucasian population, with comparable safety profile. Conclusion The efficacy of incretin-based therapies in Asian patients improved glycemic parameters in a higher magnitude on some glycemic parameters compared with those in Caucasian population. These results indicate that incretin-based therapies may be more effective in Asian population than in Caucasian. (Med J Indones 2010; 19: 205-12)